The role of habitat choice in micro‐evolutionary dynamics: An experimental study on the Mediterranean killifish Aphanius fasciatus (Cyprinodontidae). Issue 24 (1st November 2017) - Angeletti, Dario; Sebbio, Claudia; Carlini, Alessandro; Strinati, Claudia; Nascetti, Giuseppe; Carere, Claudio; Cimmaruta, Roberta
Abstract: Habitat choice is defined as a nonrandom distribution of genotypes in different microhabitats. Therefore, it could exert a great impact on the genetic variance of natural populations by promoting genetic divergence, local adaptation, and may even lead to sympatric speciation. Despite this potential role in micro‐ and macro‐evolutionary processes, there is little empirical evidence that the various genotypes within a population may differ in habitat choice‐related behaviors. Here, we tested whether habitat choice may have contributed to genetic divergence within a local population of the Mediterranean killifish Aphanius fasciatus, which emerged between groups inhabiting microhabitats with different oxygen concentrations during previous field studies. In a first experiment, we studied the distribution of individuals in conditions of hypoxia and normoxia to test whether they had a different ability to shy away from a hypoxic environment; in a second experiment, we analyzed the individual behavior of fish separately in the two conditions, to verify whether they showed peculiar behavioral responses linked to a possible differential distribution. We then analyzed the six allozyme loci, whose allelic and genotypic frequencies were significantly divergent in the previous studies. In the first test, we found that the distribution of the two homozygote genotypes of the glucose‐6‐phosphate isomerase‐1 locus (GPI‐1) was significantly different between the hypoxic and the normoxic conditions. During the second test, all individuals were more active in hypoxic conditions, but the two GPI‐1 homozygotes showed a significant difference in time spent performing surface breathing, which was consistent with their distribution observed in the first experiment. These results provide evidence that individual behavioral traits, related to genetic features, may lead to a nonrandom distribution of genotypes in heterogeneous although contiguous microhabitats and, consequently, that habitat choice can play a significant role in driving the micro‐evolutionary dynamics of this species. Abstract : We experimentally tested the ability of different genotypes of the Mediterranean killifish Aphanius fasciatus to shy away from a hypoxic environment and their behavioral responses to both hypoxia and normoxia. We found that the genotypes of the glucose six phosphate isomerase‐1 loci (GPI 1) showed differences in their ability to shy away from hypoxia. Moreover, the two GPI‐1 homozygotes showed a significant difference in time spent in surface breathing, and this result can explain their difference in escaping from hypoxia. Our study suggests that individual behavioral traits related to genetic features may lead to a nonrandom distribution of genotypes in heterogeneous microhabitats.